Why we need interprofessional education to improve the delivery of safe and effective care - Scott Reeves (Faculdade de Medicina de Botucatu (Unesp), 2016)
Interprofessional education (IPE) is an activity that involves two or more professions who learn interactively together to improve collaboration and the quality of care. Research has continually revealed that health and social care professionals encounter a range of problems with interprofessional coordination and collaboration which impact on the quality and safety of care. This empirical work resulted in policymakers across health care education and practice to invest in IPE to help resolve this collaborative failures. It is anticipated that IPE will provide health and social care professionals with the abilities required to work together effectively in providing safe high quality care to patients. Through a discussion of a range of key professional, educational and organization issues related to IPE, this paper argues that this form of education is an important strategy to improve the delivery of safe and effective care